Tectocepheus punctulatus Djaparidze 1985 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 262, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444

Tectocepheus punctulatus Djaparidze, 1985 * Material – New record for Turkey. Five specimens in Aluç Dağı Natural Park, Ankara. N 40° 49′ 75.37′′, E 32° 58′ 26.46′′, alt. = 1402 m. 15 July 2018, Soil. Global distribution – Palaearctic. Ecology – All types of habitats.
Keywords: Arthropoda; Tectocepheidae; Tectocepheus punctulatus; Tectocepheus; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Taxonomy; 15. Life on land